Desenvolvimento de compósito de HDPE verde com hidroxiapatita e união com Ti6Al4V através de sobremoldagem por injeção - Morozo, Mario Augusto (Universidade Federal de São Carlos, 2023)
This thesis addresses the development of a composite of green high-density polyethylene (G-HDPE) and hydroxyapatite (HA), compatibilized with high-density polyethylene functionalized with maleic anhydride (HDPE-g-MAH). It further explores the hybridization of this nanocomposite onto a Ti6Al4V - ELI alloy through injection overmolding, focusing on biomedical applications. The study involved the synthesis (precipitation in aqueous medium) and characterization (XRD, XRF, particle size distribution, and SEM) of hydroxyapatite, extrusion and injection molding, mechanical (tensile and impact), thermal (DSC), microscopical (SEM), and in vitro biological characterization of the composites. The results were evaluated using design of experiments (DOE), analysis of variance (ANOVA), and Tukey test. The composite containing 30 wt% of HA and 30 wt% of HDPE-g-MAH (relative to the HA content in the composite) showed a good balance of mechanical properties, nearly negligible hemolysis percentage, and a mass increase of 8% during the hydrolytic degradation test. The hybrid joint of the composite with the optimized composition, injection molded onto Ti6Al4V, showed good interfacial anchoring, resulting in outstanding shear strength (3 MPa) and fatigue life (> 106 cycles). This multi-material approach has provided subsidies for the advanced manufacture of biomedical devices with optimized mechanical and biological properties, exploiting efficient processing techniques.
Development of green HDPE composite with hydroxyapatite and jointing with Ti6Al4V through injection overmolding
Keywords: Polietileno de alta densidade verde; Hidroxiapatita; Compatibilização; Sobremoldagem por injeção; Green high-density polyethylene; Hydroxyapatite; Compatibilization; Injection overmolding; ENGENHARIAS::ENGENHARIA DE MATERIAIS E METALURGICA::MATERIAIS NAO METALICOS